IMPLEMENTASI KEBIJAKAN PERDA NOMOR 14 TAHUN 2009 DALAM MENINGKATKAN KINERJA PEMERINTAH DESA PADALARANG KECAMATAN PADALARANG KABUPATEN BANDUNG BARAT - Dadang Supriatna (Jurnal Tatapamong, 2020)
Village apparatuses as elements of village government administrators who are tasked with assisting the village head, capacity village officials is still low so that they lack understanding of government policies in carrying out their duties and functions as community servants. From this, the village apparatus needs attention so that the performance of the village equipment increases. The research objective was to analyze the increase in performance village relationship between the implementation Perda increased performance. The research method uses a mix method. Data collection techniques are observation, documentation, documentation and questionnaires. The results showed less than optimal, which was caused by: 1) Not yet optimal performance of village officials in accommodating and channeling community aspirations. 2) Lack of socialization regarding new policies by the Regional Government to the Village Government 3) Limited facilities and infrastructure owned by the Village Government in providing services to the community 4) Ununderstanding of Village officials regarding Regional Government policies. 5) Lack of motivation to work village officials in Padalarang Village. From this, positive implementation PERDA No. 14 of 2009 and the performance of village officials. In this case the regional government of West Bandung district can provide guidance and evaluate the performance of village heads and village officials regularly so as to improve the performance of village officials.